The zoning strategy for smes: a marketing concept O2O (offline and online). (March 2019) - Sarkum, Sumitro; Suryadi, Sudi; Rasyid Munthe, Ibnu; Hidayat, Rahmat
Abstract: This study aims to find a concept of empowerment of SMEs through methods of socialization and promotion of SMEs products in two different markets (offline and online) using a system of engagement. This concept is expected to be a reference for the implementation of SMEs management strategies and the creation of entrepreneurial infrastructure in North Sumatra. This concept will bring benefits for SMEs to enter the digital market while still exist in traditional markets. The concept of information and communication system is integrated with social media, web and market place SMEs. Such integration can increase sales of SMEs products in traditional markets and ready to compete in the international market.